Spectrophotometric Evaluation of Color Changes of Nanohybrid and Microhybrid Resin-Composite Materials after Staining and Bleaching: An In Vitro Study - Fatin Salim Mohammed; Ali Dhahee Malallah; Nadia H. Hasan (Dental Hypotheses, 2025)
Introduction: This study evaluated the impact of coffee, tea, and Coca-Cola and bleaching with 35% H2O2 on nanohybrid and microhybrid resin-composite. Methods: Forty discs of nanohybrid and microhybrid resin-composite materials were fabricated, and their baseline color was assessed. Specimens were divided into four groups (n = 10), immersed in distilled water, tea, coffee, or Coca-Cola for 3 h/day over 40 days, followed by color evaluation. Specimens underwent bleaching with 35% H2O2 before the third color assessment. Color changes were measured using the CIE Lab system, and results were analyzed with a two-way analysis of variance at P < 0.05. Results: Both resin composites showed clinically unacceptable color change (ΔE > 3.3) after coffee, tea, and Coca-Cola immersion. Nanohybrid discs immersed in coffee showed the highest color change. The difference between the color after bleaching and the baseline color (ΔE3) was >3.3 for both composites in all groups except for the microhybrid composite in the Coca-Cola group. Conclusion:: Postbleaching, specimens showed significant color enhancement; however, they did not return to baseline color levels.